First report of field resistance to cyantraniliprole, a new anthranilic diamide insecticide, on Bemisia tabaci MED in China - Ran WANG; Jin-da WANG; Wu-nan CHE; Chen LUO (Journal of Integrative Agriculture)
The Bemisia tabaci (Gennadius) cryptic species complex comprises important insect pests that cause devastating damage to agricultural crops worldwide. In China, the B. tabaci Mediterranean (MED) (or biotype Q) species is threatening agricultural production all over the country as resistance to commonly used insecticides has increased. This situation highlights the need for alternative pest control measures. Cyantraniliprole, a novel anthranilic diamide insecticide, has been widely employed to control Hemipteran pests. To monitor the levels of resistance to cyantraniliprole in B. tabaci field populations in China, bioassays were conducted for 18 field samples from nine provinces over two years. Compared with median lethal concentration (LC50) for the MED susceptible strain, all field samples had significantly higher resistance to cyantraniliprole. Furthermore, resistance factors (RFs) increased significantly in samples from Shanxi (from 5.62 in 2015 to 25.81 in 2016), Hunan (3.30 in 2015 to 20.97 in 2016) and Hubei (from 9.81 in 2015 to 23.91 in 2016) provinces. This study indicates a considerable decrease in the efficacy of cyantraniliprole against B. tabaci and establishes a baseline of susceptibility that could serve as a reference for future monitoring and management of B. tabaci resistance to cyantraniliprole.